The Impact of Regional Infrastructure Sector Investment on Economic Growth and Regional Inequality in East Kalimantan Province, 2012–2023 - Fryma Putra Pratama; Fitriadi Fitriadi; Emmilya Umma Aziza Gaffar (International Journal of Economics, Commerce, and Management, 2025)
The study explores the impact of regional infrastructure investment on economic growth and regional inequality in East Kalimantan Province from 2012 to 2023. Motivated by the ongoing development disparities in Indonesia, especially outside Java and Sumatra, this research examines how infrastructure spending—particularly in public works, housing, and transportation—affects East Kalimantan’s economic growth and regional inequality. Using a quantitative methodology, the analysis leverages secondary data obtained from local government agencies. The research employs SPSS 23 for path analysis to evaluate relationships among variables, focusing on East Kalimantan’s fiscal allocations and their impacts on economic dynamics. The results indicate mixed impacts across sectors: while housing and transportation investments significantly promote economic growth, public works spending shows no significant effect.